IMPLEMENTASI SISTEM INFORMASI PERANGKAT LUNAK NILAI AKADEMIK SISWA - Ananto, Dennis; -, Fitria (Jurnal Informatika, 2017)
Information is very important in the relationship between parents and students with school. Needs information on the value of student exams in schools for example as a means of supporting academic activities that are very important to be known by parents of students. Submission of information on the academic value of students in schools is generally done every acceptance report cards. The system that has been generated is the development of web based exam score software designed to report the test scores to students and parents through the website. Web-based exam score software has run well. The software exam scores are implemented using the MySQL database, and PHP Codeigniter as a programming language tool.Â Keywords: Software Value Test, website, Codeigniter.